Education Quality and Opportunities for Skills Development in Albania : An Analysis of PISA 2000-2012 Results - World Bank Group (Washington, DC, 2014)
Albanian students improved their performance on PIS A1 reading, math, and science assessments between 2000 and 2012, a period over which access to upper secondary education expanded dramatically. The improvements are equivalent to a quarter to half a year of schooling in math and science and more than one year of schooling in reading. The improvements were realized despite substantial increases in enrollment and the attendant changes in the PISA sample composition. The gross enrollment rate in upper secondary education was only about 40 percent in 2000, but increased markedly to 72 percent in 2009 and 83 percent in 2012. A spike in enrollment usually results in lower average student performance due to the inclusion of poorer and traditionally excluded students. In the context of a rapidly expanding education system, it is remarkable that Albania managed to improve its average PISA scores. It is even more notable that the improvement came from significant advancements made by low-achieving students. Albania s improved PIS A scores coincide with the launch of intensive reform efforts in its education sector. The Government of Albania initiated the education sector strategy formulation process in 2002, which resulted in the 2004 passage of the National Education Strategy (NES) and the first attempt to develop a long-term roadmap for the sector. The NES served as the catalyst for a range of reforms, including: improved teacher recruitment, compensation, and management; a revised curriculum for basic and general upper secondary education; enhanced transparency and accountability through reform of the Matura, the national student assessment; reduced price and improved textbook quality through a reformed procurement process; and provision of textbook subsidies to the poorest households. While it is beyond the scope of this report to determine a causal relationship between the range of policy reforms and improved PISA scores, this report shows that socioeconomic variables played an important role. Explanatory analyses show that the effect of education variables cannot be disentangled from the effect of socioeconomic variables. Furthermore, with economic growth averaging 4.9 percent per year from 2000-2012, a viable explanation is that the general improvement in economic conditions helped to raise the tide on all social indicators, including PISA performance.